Multi-parameter optimization of aza-follow-ups to BI 207524, a thumb pocket 1 HCV NS5B polymerase inhibitor. Part 2: Impact of lipophilicity on promiscuity and in vivo toxicity. Issue 5 (1st March 2015) - Beaulieu, Pierre L.; Bolger, Gordon; Deon, Dan; Duplessis, Martin; Fazal, Gulrez; Gagnon, Alexandre; Garneau, Michel; LaPlante, Steven; Stammers, Timothy; Kukolj, George; Duan, Jianmin
Graphical abstract: Abstract: We describe our efforts to identify analogs of thumb pocket 1 HCV NS5B inhibitor1 (aza-analog of BI 207524) with improved plasma to liver partitioning and a predicted human half-life consistent with achieving a strong antiviral effect at a reasonable dose in HCV-infected patients. Compounds3 and7 were identified that met these criteria but exhibited off-target promiscuity in an in vitro pharmacology screen and in vivo toxicity in rats. High lipophilicity in this class was found to correlate with increased probability for promiscuous behavior and toxicity. The synthesis of an 8 × 11 matrix of analogs allowed the identification ofC3, an inhibitor that displayed comparable potency to1, improved partitioning to the liver and reduced lipophilicity. AlthoughC3 displayed reduced propensity for in vitro off-target inhibition and the toxicity profile in rats was improved, the predicted human half-life of this compound was short, resulting in unacceptable dosing requirements to maintain a strong antiviral effect in patients.